Day 2 Tue, November 15, 2016 2016
DOI: 10.2523/iptc-18839-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sand Production Management the Critical Challenge in Zawtika Gas Production

Abstract: To ensure safe operations and to maximize well potential, PTTEPI has formulated a sand production management strategy to reduce risks due to sand production while extracting natural gas resources from the young clastic reservoirs formed during Plio-Pleistocene geological sequence. Over the 2 years of historical production, the strategy has been fine-tuned and enhanced to improve its effectiveness in managing sand production. The strategy integrates efforts from both subsurface and surface discip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The driving force for sand production was speculated to be the water flow rate rather than the gas flow rate. This was a pioneering work, although we would now conclude that the results are limited, or at least not ideal, to cover all sanding mechanisms for HBS since sand production also arose in conventional natural gas production reservoirs with barely water production. , …”
Section: Mechanisms Of Sandingmentioning
confidence: 99%
See 1 more Smart Citation
“…The driving force for sand production was speculated to be the water flow rate rather than the gas flow rate. This was a pioneering work, although we would now conclude that the results are limited, or at least not ideal, to cover all sanding mechanisms for HBS since sand production also arose in conventional natural gas production reservoirs with barely water production. , …”
Section: Mechanisms Of Sandingmentioning
confidence: 99%
“…This was a pioneering work, although we would now conclude that the results are limited, or at least not ideal, to cover all sanding mechanisms for HBS since sand production also arose in conventional natural gas production reservoirs with barely water production. 74,75 The later experiments regarding sand production behaviors mainly focused on (1) fines migration and its influences on physical properties of the host sediment from both macroscale 56,76 and microscale 77 perspectives; (2) Multilateral coupling effect between depressurization strategies and particle migration. 77−80 (3) Influences of sand-control devices on fines production, as well as fine-induced plugging of wellbore equipment.…”
Section: Mechanisms Of Sandingmentioning
confidence: 99%
“…During the network training, after the performance gradient has reached a satisfaction pre-set goal, the training process is terminated. To demonstrate the correlation between the trained CIAD model for each of the flow measurement characteristics (c) (d) parameters and the predictors (extracted signal features) used in this study, a three-dimensional plot was used as shown inFigure 13,14, 15 and 16.…”
mentioning
confidence: 99%